Studi Penerapan Area Traffic Control System (ATCS) Di Beberapa Simpang Kota Semarang - Descraredo Henky Sunyoto; Febriansyah Ramadhan; Rudatin Ruktiningsih (G-SMART, 2019)
The increasing of transportation needs in big cities had almost a same problem, which is congestion on roads especially at the crossroads. Semarang is one of the cities located at a strategic point. Therefore, Area Traffic Control System came as a solution. Area Traffic Control System (ATCS) is a system that controlling road traffic intersections by using traffic lights where the setting of traffic light at each intersection was coordinated, so the road users could get a minimum delay. Government of Semarang plans to install  ATCS at the intersection of PRPP and Madukoro. The location of study is intersections of PRPP and Madukoro, where the intersection is a cross-city connecting route that is crossed by heavy and light vehicles and vehicles that going to and out from A. Yani airport. The method that used in this study is a survey method, including surveying traffic volume, queue length, delays, and light phase. The results then processed using a formula from the Indonesian Road Capacity Guidelines (PKJI'14). The results of this study is alternative coordination with a cycle time is 244 seconds for each intersection. Intersection I starts at 0 seconds, intersection II starts at 90 seconds. The degree of saturation obtained for the north and south PRPP intersections is 0. 28, for the east is 0. 36, for the west is 0. 42, while for intersection of north Madukoro  is 0. 35 , for the south is 0. 36, for the east is 0. 39, and for the west is 0. 45 So that the application of the Area Traffic Control System (ATCS) can have a positive resolution for reducing congestion and  get good traffic flow in the intersections of Madukoro and PRPP.